189k views
3 votes
7(37.9 + 8.7)(7 + 37.9) + (7 + 8.7) = 60.6b. (7 ~ 37.9) + (7 * 8.7) = 326.2a.C. (7 37.9) * (7 * 8.7) = 16156.77d. (7 + 37.9) < (7 + 8.7) = 704.93

User RoyalTS
by
5.4k points

2 Answers

4 votes

Answer:

I think its 704.93 I don't really know though

Step-by-step explanation:

none

User CoolMind
by
5.5k points
2 votes

Answer:

b. (7 * 37.9) + (7 * 8.7) = 326.2

Step-by-step explanation:

Given the expression:


7\mleft(37.9+8.7\mright)

Apply the left-distributive property:


\begin{gathered} =7\mleft(37.9)+7(8.7\mright) \\ =(7*37.9)+(7*8.7) \\ =265.3+60.9 \\ =326.2 \end{gathered}

An equivalent expression is Option B.

User Adam LeBlanc
by
5.4k points